2018
DOI: 10.4049/jimmunol.1701719
|View full text |Cite
|
Sign up to set email alerts
|

Mitocryptides from Human Mitochondrial DNA–Encoded Proteins Activate Neutrophil Formyl Peptide Receptors: Receptor Preference and Signaling Properties

Abstract: Phagocytic neutrophils express formyl peptide receptors (FPRs; FPR1 and FPR2) that distinctly recognize peptides starting with an N-formylated methionine (fMet). This is a hallmark of bacterial metabolism; similar to prokaryotes, the starting amino acid in synthesis of mitochondrial DNA-encoded proteins is an fMet. Mitochondrial cryptic peptides (mitocryptides; MCTs) with an N-terminal fMet could be identified by our innate immune system; however, in contrast to our knowledge about bacterial metabolites, very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…Accompanying the impairment we observed in ex vivo NET formation was a significant trauma-induced elevation in the circulating levels of the mitochondrial-derived N-formylated peptide ND6. In a recent study, suppressed chemotactic responses toward CXCL1 and LTB 4 were reported for neutrophils pre-treated with synthetic ND6 (22), a finding that mirrored results of previous studies where prior exposure to bacterial-derived N-formylated peptides or ND6 respectively was shown to reduce neutrophil migration and ROS production upon secondary stimulation (10, 26). Adding to this growing body of literature that suggests a tolerising effect for mitochondrial-derived peptides on neutrophil function, we demonstrated that neutrophils pre-treated with whole mtDAMP preparations, but not purified mtDNA, exhibited significantly reduced NET production following PMA stimulation.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Accompanying the impairment we observed in ex vivo NET formation was a significant trauma-induced elevation in the circulating levels of the mitochondrial-derived N-formylated peptide ND6. In a recent study, suppressed chemotactic responses toward CXCL1 and LTB 4 were reported for neutrophils pre-treated with synthetic ND6 (22), a finding that mirrored results of previous studies where prior exposure to bacterial-derived N-formylated peptides or ND6 respectively was shown to reduce neutrophil migration and ROS production upon secondary stimulation (10, 26). Adding to this growing body of literature that suggests a tolerising effect for mitochondrial-derived peptides on neutrophil function, we demonstrated that neutrophils pre-treated with whole mtDAMP preparations, but not purified mtDNA, exhibited significantly reduced NET production following PMA stimulation.…”
Section: Discussionsupporting
confidence: 77%
“…For instance, it has been shown in vitro that monocytes pre-exposed to mtDNA (25) and neutrophils pre-treated with whole mtDAMP preparations (23) exhibit impaired cytokine production and calcium mobilization respectively upon secondary stimulation. Furthermore, a significant reduction in stimulus-induced ROS production and transmigration was reported for neutrophils pre-exposed to bacterial-derived or synthetic N-formylated peptides (10, 22, 26), both of which signal through the same formyl peptide receptor (FPR) as mitochondrial-derived formyl peptides. Based on these observations, the concept of mtDAMP-induced tolerance has been coined and proposed to be a potential mechanistic explanation for the state of peripheral neutrophil dysfunction that develops in the aftermath of major trauma (10, 22).…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophil-expressed FPR1 and FPR2 belong to the large family of G protein-coupled receptors (GPCRs) and display high affinity for formylated peptides of both bacterial and host mitochondrial origin (10,11). To date, all characterized mitochondrial-derived formyl peptides trigger, despite differences in FPR preference, similar signaling and functional responses that include a G protein-dependent rise in the cytosolic concentration of free calcium ([Ca 2+ ] i ) through the PLC-PIP 2 -IP 3 pathway and the release of reactive oxygen species (ROS) generated by the phagocyte NADPH oxidase (12). In addition to formyl peptides, both FPR1 and FPR2 recognize also a number of endogenous and exogenous inflammatory mediators as well as synthetic compounds that lack the formylated methionine hallmark (13,14).…”
mentioning
confidence: 99%
“…The P4Pal 10 pepducin abolished WKYMVM-induced O 2 − production, and the inhibition was P4Pal 10 concentration dependent with an IC 50 -value of ∼ 0.7 µM (Fig 3A). To further investigate whether the inhibitory effect of P4Pal 10 is restricted to the agonist WKYMVM or achieved on the level of FPR2, we used several other FPR2 selective agonists including the Staphylococcus aureus -derived PSMα2 peptide (28), the mitochondrial-derived MCT-ND4 peptide (29), the lipidated peptidomimetic agonist Compound 14 (13), and the activating FPR2 specific pepducin F2Pal 10 (12, 30). All these FPR2 agonists activate neutrophils and P4Pal 10 inhibited the response (Fig 3B).…”
Section: Resultsmentioning
confidence: 99%